Azienda Sanitaria Locale Roma 4: the external evaluation as strategy to improve vaccination services. (13th November 2019) - Fusillo, C; Sinopoli, M T; Morucci, L; Marchetti, C; Quintavalle, G
Abstract: Issue: Azienda Sanitaria Locale (ASL) Roma 4 is one of the ten local healthcare companies of Lazio Region. Vaccination Service (VS), organized in 15 ambulatories, is managed by dedicated and trained staff and this organization has led to high vaccination coverage over the years. In 2017, the National Immunization Plan and the new law on mandatory vaccination required a reshaping of VS. The Health Management of ASL Roma 4 has requested an external evaluation of the VS to a private company (PC) with the aim to highlight weaknesses and strengths. Description of the problem: The PC, through inspections and questionnaires addressed to personnel, analysed four features: amplitude of the access to the ambulatory; management of the access; communication; tools. The analysis focused specifically on vaccination for people under 18 years old. Results: The PC underlined these weaknesses: massive free access; strong influx of users from other adjacent ASL; computerized vaccination registry not available online; absence of a centralized booking and information request system; lack of targeted use of social networks. Best practices of the VS are: vaccination stocks centrally managed; preventive interview for travellers; structured procedures shared throughout the territory; focused vaccination campaigns; information material sent to the families of the new born; online portal available to users to view their personal data and download vaccination certificates; vaccination counselling; openings dedicated to specific user categories. Lessons: The PC suggested these solutions: division of ambulatory opening into free access and booking/active call; online computerized registry; unique call center constitution; creation of official social network pages. ASL Roma 4 activated the unique call center and taken corrective actions for the other weaknesses. Key messages: Best practices can be used in other healthcare setting and the periodically external evaluations can improve the vaccination service. Continuously monitoring the activities improves the quality of the vaccination service.